Selection On synonymous Mutations Revealed by 1135 Genomes of Arabidopsis thaliana. (April 2020) - Wei, Lai
Synonymous mutations do not change the amino acid but do change the synonymous codon usage. In genomes of different organisms, the gene conversion process is biased toward GC, which is irrespective of mutation bias. In the coding region, this trend is especially obvious and it is possibly caused by the preference on G/C-ending codons over the A/T-ending ones. If the G/C-ending codons are advantageous, then the synonymous mutations that change A/T to G/C would be "optimal" compared to the opposite ones. In theory, one should observe signals of positive selection on these optimal synonymous mutations. The recently released single-nucleotide polymorphism (SNP) data from the 1001 genome project of Arabidopsis thaliana provided researchers with an unprecedented opportunity to verify this assumption. I fully take advantage of the SNP data from 1, 135 A thaliana lines and came to the conclusion that synonymous mutations in natural populations are not strictly neutral: the synonymous mutations that increase GC content (from A/T to G/C) tend to have higher derived allele frequencies (DAFs) and, therefore, are likely to be positively selected. My current study broadens our knowledge of the selection patterns of synonymous mutations and should be appealing to evolutionary biologists. One sentence summary: In 1135 genomes of Arabidopsis thaliana, the synonymous mutations that increase the GC content tend to have higher derived allele frequencies (DAFs) and are likely to be positively selected.